Characteristic manifestations of uncertainty tolerance in persons working with custody records - Stoyatska , Ganna (Psychological Prospects Journal, 2022)
Purpose. The article is devoted to the study of some psychological traits of people who work with the system of custody records and the peculiarities of their response to uncertainty situations. The results of an empirical study conducted during the summer and autumn of 2021 among National Police officers involved in escorting and serving as human rights officers are presented. Custody records, as an innovative electronic tool for video recording and surveillance, requires employees to pay more attention to their own professional actions, which can lead to stress and intolerance to work in conditions of novelty and uncertainty. The conceptual hypothesis of the study was the assumption that there are significant differences between positive, negative or neutral assessment of the need to work in the custody records context and respondents individual tendencies to consider and evaluate uncertain situations as desirable or, in case of intolerance into uncertainty, undesirable.Methods. Discriminant analysis was chosen as the main research method. Taking into account the specifics of the sample, the psychodiagnostic methodology used in the study had to comply with the guidelines for use in the system of the Ministry of Internal Affairs of Ukraine. We used Stanley Badner's Intolerance of Ambiguity Scale (IAS) (Ukrainian-language adaptation by Barko V.I. and Ostapovich V.P.).Results. The main results of the study include the establishment of a high level of connection between the attitude to professional responsibilities in the functioning of custody records and such a characteristic feature of personality as a "source of intelligence complexity."Conclusions. This study emphasizes the importance of understanding how law enforcement officers treat professional activities in the presence of external independent control over the processes that take place in a closed special institution.
Keywords: custody records, tolerance for uncertainty, intolerance sources, novelty, complexity, unsolvability.